2016
DOI: 10.1002/2016jd025057
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence dependence on winds and stability in a weak‐wind canopy sublayer over complex terrain

Abstract: The daytime and nighttime turbulence profiles within a weak‐wind forest canopy were investigated by using data collected within a temperate mixed conifer canopy in northern Idaho, USA. Turbulence measurements made at three heights on a single tower within a Douglas fir canopy were compared. Data were split between the daytime and nighttime to determine the relationships among the local temperature gradient, wind direction, wind speed, and turbulence levels. The total flow field distributions and vertical stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…This was more evident at 0.21 h where there was the added influence of the ground and understory components. Conditions at 0.21 h were more closely tied to the slope direction [ Russell et al ., ] and hence the stronger similarities between the wind direction spectra than at the other two heights.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was more evident at 0.21 h where there was the added influence of the ground and understory components. Conditions at 0.21 h were more closely tied to the slope direction [ Russell et al ., ] and hence the stronger similarities between the wind direction spectra than at the other two heights.…”
Section: Resultsmentioning
confidence: 99%
“…Russell et al . [] showed that the lowest heights at this site were the most adherent to the bimodality of sloped flow, but it remains unclear as to how this translates to the turbulence structure. Does the depth within the canopy dictate the general shape of the spectra or is it a combination of stability and wind direction?…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al . () have proposed that the SBL regime may be determined from the relationship between a turbulence‐related quantity, such as the turbulence velocity scale ( V TKE ) or the friction velocity (u*) and the mean wind speed (Vtrue‾), and this criterion has been used for that purpose by a large number of studies since (Martins et al ., ; Mahrt et al ., ; Russell et al ., ; Dias‐Júnior et al ., ; Vignon et al ., ; Acevedo et al ., ; inter alia ). The comparison between V TKE and Vtrue‾ from the simulations shows that they have a linear relationship for the first hours of the simulation (Figure ), deviating from it later.…”
Section: Temporal and Vertical Structurementioning
confidence: 97%
“…The very small TKE and heat flux, as well as the reduced cooling rate at the end of the simulations, indicate that the surface layer is in the very stable regime and, therefore, that the SBL has experienced the transition from weakly to very stable. Sun et al (2012) have proposed that the SBL regime may be determined from the relationship between a turbulence-related quantity, such as the turbulence velocity scale (V TKE ) or the friction velocity ( * ) and the mean wind speed ( ), and this criterion has been used for that purpose by a large number of studies since (Martins et al, 2013;Mahrt et al, 2015;Russell et al, 2016;Dias-Júnior et al, 2017;Vignon et al, 2017;Acevedo et al, 2018;inter alia). The comparison between V TKE and from the simulations shows that they have a linear relationship for the first hours of the simulation (Figure 2), deviating from it later.…”
Section: Temporal and Vertical Structurementioning
confidence: 99%
“…Other criteria that make use of a transition wind speed have been explored (Van Hooijdonk et al 2015;Sun et al 2012). The HOST criterion was first applied to the 1999 Cooperative Atmosphere-Surface Exchange Study (CASES-99) (Sun et al 2012) and has been applied in several subsequent studies (i.e., Mahrt et al 2015;Russell et al 2016;Maroneze et al 2019). The criterion relates the mean horizontal wind speed to the turbulent intensity at a given height.…”
Section: Resultsmentioning
confidence: 99%